Physicochemical characterization of welding and grinding fine particulates at a machinery plant: A comprehensive case study of workers’ health risk assessment - Yen, Po-Hsuan; Chung, Hsin-Nan; Cheng, Wen-Hsi; Yuan, Chung-Shin; Tseng, Yu-Lun; Yeh, Chin-Ko; Lien, Chang-Hua; Cheng, Su-Wen (Atmospheric Environment: X, 2025)
Electric welding is a well-developed technology and an indispensable process in today's metal processing-related manufacturing industries. However, high-temperature operation could easily expose welding personnel to metal fume containing particle matters (PM) with aerodynamic diameters (dp) ranging from sub-microns to microns. This investigation focused on a high-pressure vessel manufacturing factory in southern Taiwan, and workers in the same indoor factory building were divided into five similar exposure groups (SEGs), including design, layout/assembling, arc welding, grinding and pickling/painting, to implement personal sampling. According to the monitoring data on-site, high concentrations of PM are mainly found in the areas within 0.5 m of welding operations; the fume produced from ilmenite electrodes has the highest concentration of PM, and followed by those using high-fiber electrodes and high-tensile steel electrodes. Especially when welding with ilmenite electrodes at the current of 150 A, the concentrations of PM2.5 and PM10 reached the highest 1716 and 3024 μg/m3, respectively. The SEG of welding, who manually welded carbon steel and stainless steel, even exposed to submicron particles with dp = 151–170 nm. Metal analysis of PM using inductively coupled plasma optical emission spectroscopy (ICP-OES) found that the cancer risk of cadmium (Cd) and chromium (Cr(VI)) in the SEG of pickling and painting was significantly the highest among all SEGs; the non-cancer risk (hazard index) of manganese (Mn) was high among all SEGs. •Workers in an indoor machinery plant were performed personal samplings for welding fumes.•The fume produced from ilmenite electrodes had the highest concentration of PM.•MMA welders of carbon steel and stainless steel were exposed to submicron PM.•Cancer risks of pickling/painting workers and Argon welders were significantly high.•Non-cancer risk of Mn was high among all types of processes on-site.